Key Mechanistic Features in Palladium-Catalyzed Methylcyclopropanation of Norbornenes With Vinyl Bromides: Insights From DFT Calculations - Ying, Fang; Zhang, Yutong; Xiang, Chuyue; Song, Zhijun; Xie, Hujun; Bao, Weiliang (Frontiers in Chemistry, 2019)
DFT calculations were performed to elucidate mechanistic details of an unusual palladium-catalyzed methylcyclopropanation from [2 + 1] cycloadditions of (Z)-2-bromovinylbenzene and endo-N-(p-tolyl)-norbornenesuccinimide. The reaction proceeds via oxidative addition, intermolecular alkene insertion, deprotonation/protonation, intramolecular alkene insertion, β-H elimination and reductive elimination, with protonation being the rate-determining step with an overall barrier of 28.5 kcal/mol. The sources of two protons for protonation and exchange have also been clarified and the calculations agree with experimental observations.